2013
DOI: 10.1016/j.ijsu.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of dexmedetomidine on the liver and remote organs against hepatic ischemia reperfusion injury in rats

Abstract: This study demonstrated that dexmedetomidine markedly reduced the oxidative stress in serum, liver, and remote organs induced by hepatic IR injury, and ameliorated the histopathological damage in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 33 publications
4
56
0
Order By: Relevance
“…An experimental study results showed that DEX administration before I/R injury caused to decrease total antioxidant capacity and PON1 activity in rats with hepatic I/R injury [8]. In our present study PON1 levels in Pp only group were significantly lower than DEX administration without Pp group.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…An experimental study results showed that DEX administration before I/R injury caused to decrease total antioxidant capacity and PON1 activity in rats with hepatic I/R injury [8]. In our present study PON1 levels in Pp only group were significantly lower than DEX administration without Pp group.…”
Section: Resultssupporting
confidence: 48%
“…Dexmedetomidine (DEX) is an adjuvant anesthesic drug that has sedative, hypnotic and analgesic potency. DEX can be used as an adjuvant anesthesic drug and some experimental and clinical studies demonstrated that DEX has protective effects against injury in the oxidative stress since it attenuates the inflammatory response [6][7][8][9][10][11]. There are various biochemical markers that indicative of oxidative stress and antioxidant defense system and which were also used to investigate the effects of DEX against I/R injury [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Dexmedetomidine has been shown to have organ protective effects in animal models particularly in modulation of cytokine and inflammatory mediators in variety of ischaemia and ischemic-reperfusion injury in animal [78][79][80][81][82][83]. However, such protective effects are not evident in human studies.…”
Section: Dexmedetomidine and Organ Protectionmentioning
confidence: 99%
“…One study has demonstrated that use of dexmedetomidine in post-bypass period in coronary bypass surgery had lower incidence of acute kidney injury [84]. Few other animal experimental study has shown organ protective effects of dexmedetomidine on myocardial protection [82,85] neuronal protection in spinal cord injury [86][87][88][89], reduction in cerebral vasospasm after sub-arachnoid haemorrhage, [89] prevention of retinal apoptosis in retinal ischaemia [90], preventive effects in Acute lung injury [91], visceral and renal protection in ischemic-repurfusion injury [81][82][83][84]92,93]. The ability to protect against organ dysfunction, notably myocardial, renal and neuronal, may yet to be the defining characteristic of this class of drug in human being.…”
Section: Dexmedetomidine and Organ Protectionmentioning
confidence: 99%
“…Even though the only slight significant difference that could be traced in OSI was between control fishes from Assiut and monosex fishes from Beheira OSI of fishes of two other sex reversed culture medium was slightly higher, but not significantly, than that of non-manipulated fishes. Actually, this biodiagnostic reflector increased in additional several oxidative stress-linked models as hyperoxia in Atlantic cod, arsenite toxicity in goldfish, diabetes, hepatic ischemia/ reperfusion, and iron overload-induced cardiac dysfunction in rats [57][58][59][60]. Elevation of OSI of hormonally masculinized fishes could be due to increased TPX and decreased TAC.…”
Section: Parameters/ Governmentsmentioning
confidence: 99%